(3CSQGQ MaX GdbQBf GdcQje (B/s - (3HGOhjdGf, CMeO Hf SGdes ((3GdQjGV (B- (3GdeedcI GdYQHjI GdSYhOjI (B:s (3OGQ GdMVGQI ddfTQ hGdJhRjY ,s, 2007)
(3jJfGhd cJGH (B((3CSQGQ MaX GdbQBf GdcQje(B) (3hGdPj bGe HJCdjag CMeO Hf SGde HGOhjdGf, ehVhY (B((3GdbQBf GdcQje(B) (3GdcJGH OYhI Edi cd eSde hddCeI HCSQgG Cf JgH dEYdGA TCf GdbQBf GdcQje aj GdbdhH ChdG, Ke aj GdhGbY GdPj jYjThfg bQGAI hMaXG hYdeG hJYdjeG hJMGceG hJTQjYG, ajMdhG MdGdg hjMQehG MQGeg, hjbjehG MQhag hMOhOg, hef CLd cd eG SHb hZjQg eeG dG jJSY GdebGe dPcQg, LGA gPG GdcJGH djchf OGaYG dENhGffG GdeSdejf; djVGYahG LghOge aj GdEgJeGe HcJGH QHge, hdjchf fhYG ef GdfUM ddeSdejf hJYGhfG Ydi GdHQ hGdJbhi (B. s
Keywords: (3GdbQBfs -- (3JLhjOs -- (3OQGSI hJYdjes -- (3MaX GdbQBfs -- (3JYdje GdbQBfs